Stability of college rankings: A study of relative earnings estimates applying different methods and models on Swedish data - Marie Gartell (Institute for Labour Market Policy Evaluation (IFAU), 2009)
The ranking of colleges varies both across methods and model specifications. Still, earnings equations tend to be consistent with regard to which colleges that on average are found in the top and bottom half of the earnings distribution. Moreover, there are no systematic differences in the ranking of colleges dependent on the age of the college, i.e. old versus new colleges. Although ranking by earnings equations provide some information about the relation to earnings, endogeneity issues preclude any causal interpretation of the rankings presented here.
Keywords: I21; J16; J24; J31; J44; 330; University education; college choice; ranking; Hochschule; Ranking-Verfahren; Absolventen; Lohn; Arbeitsverhältnis; Schweden